Formulation of lipsome-encapsulated diclofenac for improved anti-inflammatory efficacy and reduced systemic toxicity - Goh, Jun Zheng (2016)
Diclofenac, a frequently prescribed nonsteroidal anti-inflammatory drug for the treatment of various musculoskeletal disorders and pain management therapies, is frequently associated with low bioavailability and delay onset of therapeutic activities. A prolonged administration of diclofenac also leads to multiple undesired adverse drug reactions such as gastrointestinal, hepatic and renal complications. In the present work, liposomal drug delivery system, a promising lipid-based nanoparticle technology, was exploited with the aim to improve the therapeutic efficacy and reduce toxicity of diclofenac. Different in vitro and in vivo experimental models were employed to attain a proof of concept, as well as to gain insight into the mechanisms underlying present diclofenac liposomal oral formulation. A validated, rapid and reproducible proliposomes method for the preparation of liposomes-encapsulated diclofenac was successfully developed. The optimized liposomal formulation (Pro-Lipo™ Duo from Lucas Meyer, France; DMSO solvent; 16 mg diclofenac per 1 g Pro-Lipo™; 10 hours hydration time; no size reduction treatment) yield a homogenous liposomes population (polydispersity index = 0.15) with small particle size (244.3 nm), the formulation also shown highest drug entrapment (581.4 μg/g Pro-Lipo™) and exhibited a satisfactory entrapment efficacy of 91.2 %. The prepared liposomes-encapsulated diclofenac was stable in refrigerated temperature (2-8 °C) for at least 4 weeks. In Lipopolysaccharideinduced RAW 264.7 murine macrophage model, the potential of present optimized liposomal diclofenac formulation in reducing both cytotoxicity and in vitro inflammatory responses were demonstrated. Liposomes-encapsulated diclofenac exhibited a significantly (P<0.05) stronger inhibition of proinflammatory mediators (NO, TNF-α, IL-1β, IL-6 and PGE2) than the conventional diclofenac formulation of equivalent dosage. Present research work also demonstrated that intragastrically administered liposomes-encapsulated diclofenac was able to improve the drug’s therapeutic effects in various in vivo experimental models with percentage inhibition of inflammation up to 78.7 %. Paw edema test of multiple inducers (carrageenan, histamine, serotonin and formalin), carrageenan-induced granuloma pouch test and cotton pellet-induced granuloma test showed that liposomes-encapsulated diclofenac possessed a significantly (P<0.05) stronger acute and chronic anti-inflammatory activities than diclofenac, even if lower drug dosage were used to treat animals, percentage inhibition of inflammation ranging from 51.1 % to 61.9 % were observed. The improved in vivo drug therapeutic efficacy were attributed to the enhanced inhibition of pro-inflammatory mediators, including TNF-α, IL-1β, IL-6 and COX mediated PGE2 synthesis cytokines (improved in percentage of inhibition up to 63.7 %), as well as suppression of NO production (46.6 %) in animals. In addition, sub-acute toxicity study revealed that animal models treated with liposomal formulation exhibited less signs of toxicity. Biochemical analysis (liver and kidney function tests) as well as histopathology assessment indicated that present liposomal formulation was able to significantly (P<0.05) reduce diclofenac-induced organ (stomach, liver and kidney) toxicity, with reduced macroscopic and microscopic gastric lesion in repeatedly treated rats. The highest percentage of improvement for stomach, liver and kidney lesion score were observed to be at 45.1 %, 25.7 % and 22 %, respectively. In conclusion, present research work successfully developed a practical liposomal diclofenac formulation with improved therapeutic efficacies and reduced systemic toxicities.